Association between body mass index and the composition of leucocyte-poor platelet-rich plasma: implications for personalized approaches in musculoskeletal medicine - Platzer, Hadrian; Bork, Alena; Wellbrock, Malte; Pourbozorg, Ghazal; Gantz, Simone; Sorbi, Reza; Mayakrishnan, Ravikumar; Hagmann, Sébastien; Bangert, Yannic; Moradi, Babak (Current issues in molecular biology, 2025)
Platelet-rich plasma (PRP) has gained attention in regenerative medicine due to its bio-active proteins with tissue-healing potential. However, heterogeneity in PRP composition remains a major challenge for reproducibility and standardization. Given that body mass index (BMI) affects systemic blood parameters, we investigated whether BMI affects the cellular and molecular composition of PRP. Seventy-three participants were stratified into normal weight, overweight, and obese groups. PRP was prepared using a double-syringe system, and platelet activation was induced by freeze-thaw cycles. Whole blood and PRP cell counts were analyzed, and IL6, IGF1, HGF, and PDGF-BB levels in PRP were quantified by ELISA. Platelet enrichment and levels of IGF1, HGF, and PDGF-BB in PRP did not significantly differ between BMI groups. In contrast, IL6 concentrations were higher in normal-weight compared to overweight and obese individuals. Moreover, BMI-related associations emerged between platelet counts and PDGF-BB, and between PRP proteins and sex or caffeine intake, suggesting a more complex BMI-specific modulation of PRP composition. In conclusion, our findings support considering BMI as a relevant factor in PRP therapy. Incorporating BMI into PRP standardization strategies could improve reproducibility and support personalized regenerative approaches.